2014
DOI: 10.1002/gps.4219
|View full text |Cite
|
Sign up to set email alerts
|

How does ageing affect the impact of medically unexplained symptoms and medically explained symptoms on health‐related quality of life?

Abstract: Our results show that age affects the association between MUS and HRQoL, which suggest that older persons cope better with MUS than younger persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
4
13
2
2
Order By: Relevance
“…Mean age was highest in the SH2 group (48.0 ± 10.3), followed by the SH1 (44.9 ± 8.6) and the healthy (41.0 ± 8.9) group (p < 0.001). These ndings are consistent with an earlier study which reported that males take physical illness or injury less seriously and are less sensitive than females, and with an existing study that reported that an increase in age leads to physical and mental illnesses (30)(31)(32).…”
Section: Discussionsupporting
confidence: 92%
“…Mean age was highest in the SH2 group (48.0 ± 10.3), followed by the SH1 (44.9 ± 8.6) and the healthy (41.0 ± 8.9) group (p < 0.001). These ndings are consistent with an earlier study which reported that males take physical illness or injury less seriously and are less sensitive than females, and with an existing study that reported that an increase in age leads to physical and mental illnesses (30)(31)(32).…”
Section: Discussionsupporting
confidence: 92%
“…In clinical practice, patients with MUS and/or somatoform disorders are present in different settings in the health care system. Studies on clinical samples of patients with somatization are therefore even more difficult to generalize [61].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In addition, nonorganic disorders have detrimental effects on the patient's quality of life. 12 The purpose of this article is to illuminate the current state of understanding of medically unexplained symptoms and to establish basic heuristic principles of their management. It is important that clinicians take an interest in medically unexplained symptoms not only because an enormous amount of healthcare and quality of life costs are associated with them but also because these patients often present in primary care settings.…”
mentioning
confidence: 99%